2011
DOI: 10.5433/1679-0359.2011v32n3p855
|View full text |Cite
|
Sign up to set email alerts
|

Seletividade de herbicidas à cultura do milho e ao capim-braquiária cultivadas no sistema de integração lavoura-pecuária

Abstract: O objetivo deste trabalho foi avaliar a seletividade de diferentes herbicidas à cultura do milho e a Brachiaria ruziziensis cultivadas no sistema de integração lavoura-pecuária. O experimento foi conduzido no Município de Nova Xavantina -MT, no período de janeiro a junho de 2008, em solo classificado como Latossolo Vermelho distrófico. O delineamento experimental utilizado foi o de blocos ao acaso, com quatro repetições, sendo avaliados 11 tratamentos: lactofen (96 g ha -1 ); lactofen (192 g ha -1 ); carfentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
7

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 7 publications
1
4
0
7
Order By: Relevance
“…Both lactofen and fomesafen herbicides presented toxic action on dicot weeds (Petter et al, 2011); this supports the found data, since they were the herbicides that less influenced the number of basal and aerial tillers in congo grass.…”
Section: Phytotechnical Datasupporting
confidence: 88%
See 1 more Smart Citation
“…Both lactofen and fomesafen herbicides presented toxic action on dicot weeds (Petter et al, 2011); this supports the found data, since they were the herbicides that less influenced the number of basal and aerial tillers in congo grass.…”
Section: Phytotechnical Datasupporting
confidence: 88%
“…Lactofen and fomesafen present broadleaf killer character, but when they are applied on cultures that are considered tolerant, they show low selectivity, displaying moderate injury level (Petter et al, 2011). Both of them act inhibiting the photosynthetic process of weeds, and cause lipid peroxidation in non-target plants, with consequent damage to the plasma membrane (Cataneo et al, 2005); thus, it is possible to explain the fact that both species have presented intoxication symptoms, due to injuries caused by herbicide contact with leaves of the studied species.…”
Section: Intoxicationmentioning
confidence: 99%
“…Os resultados observados nesta pesquisa indicam que em virtude da grande exigência de N por ambas as espécies, quando consorciadas simultaneamente, pode haver competição pelo nutriente (BORGHI & CRUSCIOL, 2007) e que este fato pode ser agravado pelo maior número de plantas da forrageira. Alguns autores (JAKELAITIS et al, 2005;TRIGUEIRO et al, 2007;PETTER et al, 2011) …”
Section: Resultsunclassified
“…), uma vez que o milho é uma cultura difundida e possui grande adaptabilidade à diversidade edafoclimática existente no Brasil (TOWNSEND et al, 2011). Já a forrageira pode ter dupla aptidão nesse consórcio, servindo como volumoso para o rebanho bovino a partir do final do verão até o início da primavera e para formação de cobertura morta, visando à implantação do sistema de plantio direto (PETTER et al, 2011).…”
Section: Introductionunclassified